Moral Injury among Transplant Providers: Evaluating the Effects of Training in End-of-Life Counseling - David, Hannah; Rosell, Tarris; Hughes, Dorothy (Kansas Journal of Medicine, 2023)
Introduction. Ethical issues are pervasive in healthcare, but few specialties rival the moral complexity of transplant medicine. Transplant providers must regularly inform patients that they are no longer eligible to receive a potentially life-saving operation and the stress of these conversations poses a high risk of moral injury. Training in end of life counseling (EOLC) has been shown to significantly reduce provider stress and burnout. We hypothesized that training in EOLC reduces levels of moral injury among transplant providers. Methods. This was a mixed methods study. A survey was administered to staff in the solid organ transplant department at the University of Kansas Health System. Providers indicated whether they had received training in EOLC and completed the standardized Moral Injury Symptom Scale-Healthcare Professionals version (MISS-HP). A two-sample, one-sided t-test compared levels of moral injury between trained and untrained staff. Subsequently, semi-structured interviews were conducted with transplant providers, and inductive coding followed by thematic network analysis was performed. Results. Thirty-seven percent of respondents reported a moral injury score at or above the threshold for psychosocial dysfunctioning associated with moral injury. Analysis revealed no difference in moral injury scores between the trained and untrained groups (p=0.362, power=0.842). Ten participants were interviewed. Thematic network analysis demonstrated high-level themes of “challenges”, “training” and “stress relief”. Conclusions. Our study demonstrated a concerning prevalence of moral injury among transplant providers and suggested that EOLC training does not significantly mitigate the threat of moral injury.